Examining the Potential Benefits and Ethical Risks of GenAI in Lesson Planning: A TAM Approach - Estocapio, Vyoana; Bilog, Ruffa Mae; Cacananta, Jessica; Corpuz, Jea Marie; Ibasan, Bonny; Paneda, Sheikka; Asuncion, Raphael Job (Journal of Teaching and Learning, 2025)
Generative Artificial Intelligence (GenAI) is a transformative technology in education, especially in lesson planning (LP). This research examines pre-service teachers' (PSTs) perceptions of GenAI benefits and ethical risks in LP, with consideration for the Technology Acceptance Model (TAM). The findings show that PSTs are generally cognizant of the benefits and ethical ramifications of GenAI use. PSTs demonstrated a positive attitude toward integrating GenAI in lesson planning and recognized the relevance and varying levels of incorporation into their current practice. The data also highlighted that the relationship of key TAM variables influenced how PSTs view and adopt GenAI. The findings provided support for the collect construct of perceived usefulness (PU) and perceived ease of use (PEU) mediating the relationship between attitude (ATT) and use (AU). These findings contributed relevant information to inform teacher education, illustrating the need for training that balances the practical benefits and ethical dimensions of GenAI. This research can serve as a starting point for future research, curricular design, and policy making regarding the responsible and informed use of GenAI in teacher preparation.